Deep Sequencing-Based Transcriptome Profiling Reveals Avian Interferon-Stimulated Genes and Provides Comprehensive Insight into Newcastle Disease Virus-Induced Host Responses - Liu, Weiwei (Viruses, 2018)
Newcastle disease virus (NDV) is an avian paramyxovirus that causes significant economic losses to the poultry industry worldwide, with variations in NDV pathogenicity due to the differences in virulence between strains. However, there is limited knowledge regarding the avian innate immune response to NDV infection. In this study, transcriptional profiles were obtained from chick embryo fibroblasts (CEFs) that were infected with the highly virulent NDV Herts/33 strain or the nonvirulent LaSota strain using RNA-seq. This yielded 8433 transcripts that were associated with NDV infection. This list of candidate genes was then further examined using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. It showed a high enrichment in the areas of cellular components and metabolic processes, with the cellular components possibly being associated with NDV pathogenicity. Among these 8433 transcripts, 3616 transcripts associated with interferon-stimulated genes (ISGs) were obtained; these transcripts are involved in metabolic processes, including protein phosphorylation and protein modification. These results provide further insight into the identification of genes that are involved in NDV infection. The global survey of changes in gene expression performed herein provides new insights into the complicated molecular mechanisms underlying virus and host interactions and will enable the use of new strategies to protect chickens against this virus.